BELAJAR BANGUN RUANG MENGGUNAKAN MEDIA KOMPUTER DI KELAS V SDN 2 BAHARU - Muhammad Yusuf; Akhmad Rakhdiani (STKIP Paris Barantai, 2022)
The purpose of this study is to improve students' understanding and learning outcomes of space building material by using computer media in grade V students of SD Negeri 2 Baharu Utara, North Pulau Laut District. Increasing student activity in mathematics learning, especially in learning materials to build spaces using computer media. The method used in this study was classroom action research. Data analysis was carried out by observation, field notes, documentation, and tests of students' ability to understand building a room using computer media. The results showed that the use of computerization in learning about building spaces can improve student understanding and learning outcomes with assessment results from 71.44% increased to 81.76%. Increasing student activity in mathematics learning can be seen from the results of cycle 1 from 58.4% increased to 71.2% and in cycle 2 from 79.2% increased to 90.4% Key words: Activities, Learning Outcomes, Computer Media, Building Space.